Apparition in The Turn of the Screw: Real or Schizophrenic Revelations? - Haque, Mohammad Azizul (Stamford Journal of English, 2013)
Stamford Journal of English; Volume 6; Page 149-155 DOI: http://dx.doi.org/10.3329/sje.v6i0.13909